The Effect of Social Networks on The Households’ Objective Welfare in The Slum Areas of Makassar City - Ridha Vivianti; Sakaria Sakaria; Buchari Mengge (Mahesa Research Center, 2022)
The aim of this research is to analyze the effect of social networks on the households’ objective welfare in the slum areas of Makassar City. This research was a quantitative study with a survey method used to obtain data from 57 respondents using questionnaire located in Pattingalloang Village. The data collection was also conducted through observation and interview. The sample was determined using simple random sampling technique and the data were analyzed using multiple linear regression test. To answer the questions, two leading hypotheses were used, i.e. (1) the effect of social network covarage on the level of households’ obejctive welfare in the slum areas, and (2) the effect of social network intensity on the level of households’ objective welfare in the slum areas. The results of the research indicate there is a significant effect of social networks on the level of households’ objective welfare in the slum areas. The effect of social network coverage on the level of households’ objective welfare is 87%, and the strength of the effect of social network intensity on the level of households’ objective welfare is 92%.